Discourse analysis of decision making episodes in meetings: politeness theory and critical discourse analysis - Nor Fariza Mohd. Nor,; Jamaluddin Aziz, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
Many management activities (e.g. negiotiation, meetings, decision making, presentation and so on) depend on the chair‟s use and control of language. Therefore, the asymmetric relation between interactants in meetings needs to be considered. Participants in meetings have different positions and interests to defend and they used different ways to express and negotiate their points. The chairperson, on the other hand, is entrusted with the responsibility of managing the discussion and most importantly in making decision. This provides the chairperson with control of topics and turns, expressed through the exercise of power in language use. The present study will examine this asymmetric relations using the politeness strategies (Brown and Levinson, 1987) employed by the chairperson and the chair‟s display of power (Fairclough, 1992, Van Djik, 2001, 2006). The unit of analysis in this study is decision making episodes, using the notion of frame (Goffman, 1974), which involves shared understandings of certain conventions and norms that operate and facilitate participants to make appropriate interpretation of each others. The findings revealed that the chair in meeting 1 preferred to use negative politeness strategies, while the chair in meeting 2 tended to use bald- on- record politeness strategies. With regards to display of power, the chair in meeting 1 displayed power subtly by acknowledging the significant contributions made by members of the meeting to the final decision. The chair in meeting 2, however, was more bold and direct.